"There's intentionality behind it …": A genre analysis of EAP classroom lessons. Issue 23 (September 2016) - Lee, Joseph J.
Abstract: This genre-oriented analysis explores the rhetorical structure and linguistic features of EAP classroom lessons. The analysis is based on a corpus of 24 EAP classroom lessons taught by highly experienced IEP teachers. Using a focused Swalesian move analysis combined with corpus-based methods, the study examines the rhetorical moves in different phases of EAP lessons and frequent lexical phrases used to signal discourse organization in each phase. In addition, four EAP teachers were interviewed in order to gain insider perspectives into their discursive practices. The analysis reveals that EAP lessons consist of three major phases, each with three distinct moves, and with varying linguistic realizations. Findings suggest that these experienced EAP teachers have generated and internalized a stable lesson frame in response to the recurrent situation of providing meaningful, activity-driven, and logically organized EAP lessons. The paper concludes with a discussion of the power of Swales's move analysis in studying classroom lessons as well as implications for EAP teacher education. Highlights: The schematic structure and linguistic features of EAP lessons were analyzed. Swalesian move analysis combined with corpus-based methods and interviews were used. EAP lessons consist of three major phases, each with three distinct moves. Lesson phases consist of varying linguistic realizations of rhetorical structure. Power of Swales's move analysis in examining classroom lessons is discussed.